Hydrophilic interaction liquid chromatography of anthranilic acid-labelled oligosaccharides with a 4-aminobenzoic acid ethyl ester-labelled dextran hydrolysate internal standard. - Neville, D; Alonzi, D; Butters, T (2012)
Hydrophilic interaction liquid chromatography (HILIC) of fluorescently labelled oligosaccharides is used in many laboratories to analyse complex oligosaccharide mixtures. Separations are routinely performed using a TSK gel-Amide 80 HPLC column, and retention times of different oligosaccharide species are converted to glucose unit (GU) values that are determined with reference to an external standard. However, if retention times were to be compared with an internal standard, consistent and more accurate GU values would be obtained. We present a method to perform internal standard-calibrated HILIC of fluorescently labelled oligosaccharides. The method relies on co-injection of 4-aminobenzoic acid ethyl ester (4-ABEE)-labelled internal standard and detection by UV absorption, with 2-AA (2-aminobenzoic acid)-labelled oligosaccharides. 4-ABEE is a UV chromophore and a fluorophore, but there is no overlap of the fluorescent spectrum of 4-ABEE with the commonly used fluorescent reagents. The dual nature of 4-ABEE allows for accurate calculation of the delay between UV and fluorescent signals when determining the GU values of individual oligosaccharides. The GU values obtained are inherently more accurate as slight differences in gradients that can influence retention are negated by use of an internal standard. Therefore, this paper provides the first method for determination of HPLC-derived GU values of fluorescently labelled oligosaccharides using an internal calibrant.